Soluble P2X7 Receptor Is Elevated in the Plasma of COVID-19 Patients and Correlates With Disease Severity - García-Villalba, Julio; Hurtado-Navarro, Laura; Peñín-Franch, Alejandro; Molina-López, Cristina; Martínez-Alarcón, Laura; Angosto-Bazarra, Diego; Baroja-Mazo, Alberto; Pelegrin, Pablo (Frontiers in Immunology, 2022)
Inflammation is a tightly coordinated response against bacterial and viral infections, triggered by the production of pro-inflammatory cytokines. SARS-CoV-2 infection induces COVID-19 disease, characterized by an inflammatory response mediated through the activation of the NLRP3 inflammasome, which results in the production of IL-1b and IL-18 along with pyroptotic cell death. The NLRP3 inflammasome could be also triggered by sterile danger signals such as extracellular ATP triggering the purinergic P2X7 receptor. Severe inflammation in the lungs of SARS-CoV-2 infected individuals is associated with pneumonia, hypoxia and acute respiratory distress syndrome, these being the causes of death associated with COVID-19. Both the P2X7 receptor and NLRP3 have been considered as potential pharmacological targets for treating inflammation in COVID-19. However, there is no experimental evidence of the involvement of the P2X7 receptor during COVID-19 disease. In the present study we determined the concentration of different cytokines and the P2X7 receptor in the plasma of COVID-19 patients and found that along with the increase in IL-6, IL-18 and the IL-1 receptor antagonist in the plasma of COVID-19 patients, there was also an increase in the purinergic P2X7 receptor. Increase in COVID-19 severity and C-reactive protein concentration positively correlated with increased concentration of the P2X7 receptor in the plasma, but not with IL-18 cytokine. The P2X7 receptor was found in the supernatant of human peripheral blood mononuclear cells after inflammasome activation. Therefore, our data suggest that determining levels of the P2X7 receptor in the plasma could be a novel biomarker of COVID-19 severity.